MANAJEMEN PEMELIHARAAN AYAM BROILER SELAMA SATU PERIODE 14 MARET SAMPAI 26 APRIL 2014 DI PT. JANUPUTRA SEJAHTERA FARM YOGYAKARTA - , SYIFA AVIESSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Consuming chicken is very popular now a days. There is a high demand of its flesh. In general farming the chicken broiler just needs 6-8 weeks, that chicken has weight 1.5-2.1 kg and can be sold to be consumed. The job training was held in Januputra Sejahtera Farm, in which there were 11.300 chicken as the population. The farm is located in Mbokong village, Seyegan District at Sleman Region in Yogyakarta Spesial Province. This thesis tends to find the system of poultry farm management that applied by Januputra Sejahtera Farm. The method used for collecting the data were: observation, interview, and living experience the poultry farm. The result of farm observation and living experience showed that the farming initial preparation before DOC come was doing correction of curtain in and external curtain, drawing up and chaff of chick guard to lessen chicken risk fallen down, three days cage sanitizing before DOC come with desinfektan. For the conservancy of first week starter until fourth week of farming, on first and both heather switched by during 24 hour, for the next day heater switched on by night time and during cold weather. The drink place have there was ascertained have loaded by drinking water which have been mixed with sorbitol, obstetrical was sugar. Giving food of first week by the five times, rill in one day that was at 06.30, 10.30, 11.30, 15.00, and 19.00. Preventive treatment of disease on to given by vaccination of ND through eye and subcutan, day 12 vaccination of gumboro through drinking water. To a period farming of finisher in Januputra farm given eat twice in one day that was at 06.00 and 16.00. For the weight of target body a farming of finisher old age 43 day was weight 1,7-1,9 kg. Result of field data during a periode to farming 43 day that was population early 11.300 DOCâs and final population 10.200 DOCâs with death counted 1.040 (9,2%). Weight flatten crop was 1,84 kg with FCR 1,617 more efficient of FCR standard equal to 1,712 kg. Process of cropping in Januputra farm according to arrival by buyer of chicken.As for time cropping of chicken usually done morning, noon even till night time because hight request of consumer.